Effect of Incubation Time and Level of Fungus Myceliated Grain Supplemented Diet on the Growth and Health of Broiler Chickens - Hines, V.; Willis , W.L.; Isikhuemhen, O.S.; Ibrahim, S.L.; Anike, F.; Jackson, J.; Hurley, S.L.; Ohiman, E.I. (International Journal of Poultry Science, 2013)
A study was conducted to evaluate the effects of different incubation time and level of inclusion of Fungus Myceliated Grain (FMG) in diets of broiler chickens. The nine different dietary treatments were as follows: (1) Control-No-FMG (2) 5% FMG-14 d (3) 10% FMG-14 d (4) 5% FMG-28 d (5) 10% FMG-28 d (6) 5% FMG-42 d (7) 10% FMG-42 d (8) 5% FMG-56 d and (9) 10% FMG-56 d. Each diet was fed to 3 replicate pens of 10 chicks each in floor pens for 49 days. The 270 day-of-hatch straight-run chicks were fed FMG that included Lentinula edodes, Cordyceps sp. Ganoderam sp. and Pleurotus ostreatus incubated in grain for 14, 28, 42, or 56 days. FMG protein percentage, live weights, Eimeria oocyst, bifidobacteria counts, mortality, feed consumption, blood differential and immunoglobulins (IgA, IgG) were evaluated in this experiment. Percent protein between mushroom incubation periods differed significantly. Body weight results showed that all experimental treatments were significantly (P<0.05) different from treatment 1 (Control) for male broilers but did not differ with the females, while the overall feed intake was significantly higher for the control broilers. Fecal oocyst count showed only one treatment (2) differed significantly (P>0.05) from treatment 1 (Control). Bifidobacteria counts were highest in treatment 4 (8.071og10) when compared to the treatment 1 control (7.691og10) at week 5. Some hematological analysis values showed some elevation and decreased protein levels as the incubation time increased along with the antibody IgA and IgG titers. The results from this study suggest that the incubation time, mixture and level of FMG do not adversely affect growth and higher antibody levels in broiler chickens could enhance health as percent protein decline with increased beta-glucan and incubation time of the FMG.